Transplantation of Adipose-Derived Stem Cells Alleviates Striatal Degeneration in a Transgenic Mouse Model for Multiple System Atrophy. (6th October 2020) - Chang, Christine; Liu, Jen-Wei; Chen, Bo Cheng; Jiang, Zhe Sheng; Tu, Chi Tang; Su, Che Hung; Yang, Hsin Han; Liu, Zong Qi; Deng, Yu Chen; Chen, Chih Yu; Tsai, Sheng-Tzung; Lin, Shinn Zong; et al.
Patients with multiple system atrophy (MSA), a progressive neurodegenerative disorder of adult onset, were found less than 9 years of life expectancy after onset. The disorders include bradykinesia and rigidity commonly seen in Parkinsonism disease and additional signs such as autonomic dysfunction, ataxia, or dementia. In clinical treatments, MSA poorly responds to levodopa, the drug used to remedy Parkinsonism disease. The exact cause of MSA is still unknown, and exploring a therapeutic solution to MSA remains critical. A transgenic mouse model was established to study the feasibility of human adipose-derived stem cell (ADSC) therapy in vivo. The human ADSCs were transplanted into the striatum of transgenic mice via intracerebral injection. As compared with sham control, we reported significantly enhanced rotarod performance of transgenic mice treated with ADSC at an effective dose, 2 × 10 5 ADSCs/mouse. Our ex vivo feasibility study supported that intracerebral transplantation of ADSC might alleviate striatal degeneration in MSA transgenic mouse model by improving the nigrostriatal pathway for dopamine, activating autophagy for α-synuclein clearance, decreasing inflammatory signal, and further cell apoptosis, improving myelination and cell survival at caudate-putamen.